Effects The Constitutional Court Decision Allowing Marriage Agreement After Marriage (Constitutional Court Decision No. 69 / PUU-XIII / 2015) - Kevin Hanif Hakim; Akhmad Khisni (Jurnal Akta, 2019)
At first the marriage law stipulated in the Civil Law Act (Civil Code) and subsequent regulations related to marriage and even then dealt with separately by Act No. 1 of 1974 on Marriage. On October 27 2016 the Constitutional Court (MK) through its Decision No. 69 / PUU-XIII / 2015 gives constitutional interpretation of Article 29 of Act No. 1 of 1974 on Marriage which basically says that the marriage contract can be carried out during the marriage bond. Therefore, the object of the author's thesis writing is a result of the law of the Constitutional Court decision that allows marriage after marriage. And the formulation of the problem in this paper are the implications of the procedure / mechanism of making the marriage contract and the legal consequences of the status of the property as well as third parties who feel aggrieved over the agreement. Methods used by the authors te is normative research method. So as to obtain results that due to the Constitutional Court's decision that allows the marriage contract after marriage alter the legal mechanism of making the marriage contract that can now be created during the marriage bond takes place by the Notary without preceded by the determination of the competent court and the legal consequences of making the marriage contract after the wedding on the status of property together with the inherent (closely related) to the time of entry into force of the agreement and binding on third parties.Keywords: Notary; Marriage Agreement; the Constitutional Court Decision